Power cycling analysis of enameled aluminium winding wires connections pprepared with the use of SHARK-Al® type connectors - G. Kiesiewicz; T. Knych; A. Mamala; P. Kwasniewski; K. Korzen; M. Zasadzinska; A. Kawecki; P. Kowalewski (Metalurgija, 2023)
The article presents the research results of current cyclic thermal tests performed on enamelled aluminium wires connections, made with the use of a new type of Shark-Al quick-connectors. In particular, the main purpose of the conducted research was to analyse the effect of cyclic heating on the contact resistance change during the tests which allows to test the stability of the connections in simulated working conditions under current flow. Tests included a total of 300 thermal cycles, of which the first 200 were carried out to the 65 °C temperature measured in the connector at above the ambient temperature, and then additional 100 cycles were performed for the temperature of the connector at 140 °C (tolerance +5 °C). During the tests, the resistance of samples was monitored, which allowed to verify the correctness of performed connections.